A Cross-Layer Opportunistic MAC/routing Protocol to improve reliability in WBAN - Abbasi, U.F. (Institute of Electrical and Electronics Engineers Inc., 2015)
Wireless Body Area Network (WBAN) is a modern technology having a wide-range of applications. Reliability is a key performance index for WBANs, especially for medical applications. An unreliable WBAN may severely affect the patient under observation. Main causes of unreliability are inefficient routing, low transmission range, body shadowing and environmental interference. We propose a Cross-Layer Opportunistic MAC/Routing (COMR) protocol that can improve the reliability by using a timer based approach for the relay selection mechanism. The value of this timer depends on Received Signal Strength Indicator (RSSI) and residual energy. The selected relay node will have the highest residual energy and will be closest to the sink as compared to other possible relay nodes. We evaluate the performance of the proposed mechanism in terms of network lifetime, Packet Delivery Ratio (PDR), End-To-End (ETE) delay, and energy used per bit. Results depict that COMR protocol shows improvement in terms of reliability, energy efficiency, ETE delay and network lifetime in a WBAN as compared to Simple Opportunistic Routing (SOR). Â© 2014 IEEE.